SYNTACTIC STRUCTURE ANALYSIS ON DEAF STUDENT OF BRAWIJAYA UNIVERSITY - Finda Muftihatun Najihah (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This paper is aimed to investigate the syntactic structure of deaf students of Brawijaya Universirty. Syntactic structure which focuses on this discussion is the ability to recognize the sentence structure produced by deaf students. This study basically focuses on the language produced by deaf students of Brawijaya University in form of narrative writing. The narrative writing is written in Indonesian language. I chose Indonesian language as the language recourse, because the primary language of deaf students is Indonesian.This study uses descriptive qualitative research because this research basically aimed at describing the data in the form written text. The participant of this research is five deaf students who are classified into mild and moderate hearing loss. In term of analyzing the data, we concern on the three aspects of sentence structure. Those are: types of sentence, the presence of Subject and Verb in a sentence and the presence of Object for transitive verb.The finding indicates that the deaf students of Brawijaya University are able to write both simple sentences and compound sentence. They are also capable to write transitive verb which is followed by the object well. Yet, they are less in writing the passive voice form. Moreover, the data shows that different time durations of writing create a different number of words produced by them. Different deaf classification can provide different significance to a number of sentences produced by them.